Cancer and Energy Balance, Epidemiology and Overview - Berger, Nathan A.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Energy Balance and Cancer, Epidemiology and Overview is the first in a series of monographs to address the multiple facets of the world wide pandemic of overweight and obesity and its relation to cancer. This volume, authored by leading experts in their perspective fields, provides a broad and comprehensive overview of the problem from the epidemiologic viewpoint with focus on both general and special populations as well as a description of potential molecular mechanisms and reviews of the latest studies of factors impacting the association of energy balance and cancer including the effects of genetics, caloric restriction, exercise, behavior and the built environment. The collected chapters and the authors contributing to this initial volume represent a transdisciplinary approach to analyze and develop novel approaches to understand and solve what, up to now, is a globally refractory problem. The book is written to be understandable and informative to individuals from all concerned disciplines. It should serve to orient students, investigators, nutritionists, public health officials, community planners, clinicians and policy makers to the extent of the problem, its multiple dimensions and potential approaches for research and corrective interventions.
Obesity and Cancer Epidemiology -- Obesity and Cancer: Epidemiology in Racial/Ethnic Minorities -- Obesity and Cancer in Asia -- Genetic Epidemiology of Obesity and Cancer -- Obesity and Cancer: Overview of Mechanisms -- Caloric Restriction and Cancer -- Physical Activity and Cancer -- Energy Balance, Cancer Prognosis, and Survivorship -- Behavior, Energy Balance, and Cancer: An Overview -- Geographic and Contextual Effects on Energy Balance-Related Behaviors and Cancer.
Keywords: Cancer research; Pharmacology; Cancer Research; Pharmacology/Toxicology.